Comparison of the measurement of heart rate in adult free‐range chickens (Gallus domesticus) by auscultation and electrocardiography. Issue 12 (7th October 2014) - Smith, CF; Gavaghan, BJ; McSweeney, D; Powell, V; Lisle, A
<x xml:space="preserve">Abstract</x> Objective To compare the heart rates of adult free‐range chickens (Gallus domesticus) measured by auscultation with a stethoscope with those measured simultaneously using electrocardiography (ECG). Methods With each bird in a standing position, estimation of the heart rate was performed by placing a mark on paper for every 4 beats for roosters and 8 beats for hens as detected by auscultation over 30 s, while simultaneous ECG was performed. Results Heart rates measured by auscultation showed a high correlation (r = 0.97) with those measured by ECG. Conclusion There was a high correlation between the heart rates of adult free‐range chickens measured by auscultation with a stethoscope and those measured simultaneously using ECG.